(untitled) (Intent Research Scientific Journal, 2023)
The choice of acrylonitrile as the main precursor for the production of the polymer matrix is dictated by economic reasons. Acrylonitrile is an industrially available monomer, which is produced by Navoiazot JSC. However, due to changes in the world market and increased competition from foreign manufacturers of polyacrylonitrile materials, Navoiazot JSC is currently experiencing enormous difficulties in selling its products to foreign markets.